Art, intellect and politics : a diachronic perspective - Margagliotta, G. M. A.; Robiglio, Andrea A., 1972- (Studies on the interaction of art, thought and power ;, 2013)
The volume explores the relationship of artists and intellectuals from ancient Greece to modern times.